Rent-seeking Contests under Symmetric and Asymmetric Information - Cédric Wasser (Verein für Socialpolitik, 2010)
We consider a variant of the Tullock rent-seeking contest. Under symmetric information we determine equilibrium strategies and prove their uniqueness. Then, we assume contestants to be privately informed about their costs of effort. We prove existence of a pure-strategy equilibrium and provide a sufficient condition for uniqueness. Comparing different informational settings we find that if players are uncertain about the costs of all players, aggregate effort is lower than under both private and complete information. Yet rent dissipation might still be smaller in the latter settings. Numerical examples provide additional insight into the impact of the information structure.
Keywords: D72; D82; D74; 330; Rent-seeking; Contest; Asymmetric Information; Private values